Kadar Hematokrit, Urea dan Glukosa Darah Domba yang Diberi Pakan Mengandung Biji Carica Dieng - Idayanti, Rahma Wulan; Dzakiyah Nur Aziza; Adi Rahman Satrio; Hakim, Aan Lukman; Suseno, Satrio Tegar; Arifin, Mukh; Purnomoadi, Agung; Purbowati, Endang (Jurnal Ilmu dan Industri Peternakan, 2024)
This study aims to analyze the hematocrit, urea and blood glucose levels of thin-tailed sheep fed feed containing various levels of Carica Dieng seeds in complete feed. A total of 18 lams aged 3-4 months with an initial body weight of 10.68 ± 1.30 kg were fed treatment following a completely randomized design pattern: T1 = complete feed + 5% carica seeds, T2 = complete feed + 12,5% carica seeds, 5%, and T3 = complete feed + 20% carica seeds, with 6 repetitions. Blood samples for hematocrit levels were taken at weeks 2 and 9 of the treatment phase, while urea and blood glucose levels were taken at week 9, 0 hours before eating, 3 and 6 hours after being given morning food. Hematocrit levels were measured using a hematocrit reader, while blood glucose and urea levels used a scalvo analyzer. The results showed that various levels of carica seeds in complete feed had no significant effect (P>0.05) on the hematocrit, glucose and blood urea levels in sheep. The average hematocrit level at weeks 2 and 9 were 21.94 and 28.16%, the average glucose level at 0 hours was 71.22 mg/dL, and at 3 and 6 hours each was 79.00; 85.94 mg/dL. The average urea level at 0 hours, 3 and 6 hours was 30.21, 26.96 and 27.26 mg/dL. Based on the results of this study, it can be concluded that using Carica Dieng seeds in complete feed does not cause haematological disorders characterized by blood profile levels within normal limits.. Keywords: Thin-tailed Lamb, Carica Dieng, Blood Glucose, Blood urea, Hematocrit